Formulasi Masker Ekstrak Daun Pepaya (Carica Papaya L.) Sebagai Anti Jerawat - Intan Pratiwi; Youstiana Dwi Rusita (Poltekkes Kemenkes Surakarta, 2018)
Abstract Background: Mask is one of the effective facial skin cleanser. Mask has merit as deep cleansing,it’s cleaning the dirt on the skin layer deeper, binds skin cells that have died, refine pores of the skin, clean the remnants of excess fat on the surface of the skin’s face, reduce skin irritation, smoothing layer outer skin and nourish the skin, so it looks bright. This study uses papaya leaf extract has a content of the enzyme papain, alkaloids, pseudokapain, glikosid, karposid and saponins. Alkaloid contained in papaya leaves is a kind karpain which has anti bacterial activity. The advantages of the mask is the method of production can be prepared in a simple way. Masks in this study is made in the form of powder to make it easier to use and storage. Method: This study have purpose to determine the results of mask powder formulation of papaya leaf extract as an anti acne that meet the test parameters include physical, organoleptic test, water content test, pH test, and flow rate of irritation test. Result: This research is experimental observation. The results of organoleptic test mask bone-white powder, scented roses and soft textured, the results of water content of 7.5%, a flow rate of over 9 seconds, pH of 6.35. Conclusion: The results of irritation test to the 20 olunteers did not show any reaction of irritation.